2006
DOI: 10.1509/jmkg.70.2.081
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Contamination: How Consumers React to Products Touched by Others

Abstract: Although consumers like to touch products while shopping, the authors propose a theory of consumer contamination, positing that consumers evaluate products previously touched by other shoppers less favorably. The authors test the theory by manipulating cues that increase the salience that consumer contact has occurred. Furthermore, the authors investigate the role of disgust as the underlying mechanism of the theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
312
5
28

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(389 citation statements)
references
References 29 publications
25
312
5
28
Order By: Relevance
“…Indeed, the production process is not usually apparent, which can encourage consumers to use mental imagery. Past research has shown that imagined physical contact has similar effects to visible physical contact (Argo, Dahl, & Morales, 2006). In fact, contact salience plays an important role in contagion effects.…”
Section: Contagion Principlementioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, the production process is not usually apparent, which can encourage consumers to use mental imagery. Past research has shown that imagined physical contact has similar effects to visible physical contact (Argo, Dahl, & Morales, 2006). In fact, contact salience plays an important role in contagion effects.…”
Section: Contagion Principlementioning
confidence: 98%
“…In fact, contact salience plays an important role in contagion effects. It is well accepted that proximity to contact increases the likelihood of product contamination (Argo et al, 2006;Kim & Kim, 2011). People are less inclined to make a choice from a set of adjacent objects if they are informed that one object in that group is defective (Mishra, Mishra, & Nayakankuppam, 2009).…”
Section: Contagion Principlementioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, scholars have investigated consumers' willingness to pay in a variety of contexts such as its role in consumer impatience, consumer contamination, consumer satisfaction and so forth (Argo et al, 2006;Chen et al, 2005;Homburg et al, 2005;Nunes and Boatwright, 2004;Okada, 2005;Simonson and Drolet, 2004). Additionally, there is evidence that consumers' stated willingness to pay does translate into actual purchasing behavior (see Green (1992)).…”
Section: Introductionmentioning
confidence: 99%
“…Willingness to pay a higher price as a stated intent shows a preference for a store over competitors and it is not the same thing as willingness to pay which is usually measured in dollars (e.g. Argo et al, 2006) without entailing any comparisons with competition. Also, willingness to pay has sometimes been taken to be synonymous with the notion of perceived value (Bolton and Lemon, 1999;Winer, 2005).…”
Section: Introductionmentioning
confidence: 99%